SymbioCity model for sustainable urban development - Belchior-Rocha, H. (Green Chemistery 2022 - 2nd Edition of International Conference on Green Chemistry and Renewable Energy, 2022)
SymbioCity is a holistic and inclusive approach to sustainable urban development that transforms urban challenges into opportunities. Nowadays the way cities choose to respond to climate change and urban challenges is the path to the resident’s wellbeing. The objectives of this program followed the standards of the 1990s: decontamination and use of already built-up land; sustainable building materials; emphasis on public transport; limiting noise to 45 dB (through the building system) and optimising energy, water and waste services. The concept of symbiosity is very simple and has to do with the idea of transforming neighbourhoods into communities (eco-neighbourhoods) where people can live, live, work and prosper without the need to move to another part of the city or beyond, thus reducing the ecological footprint inherent in that displacement. It is not about enclosing people in ghettos, just about making mobility an option and not a necessity. Sustainable cities will be made of sets of neighbourhoods with a strong identity and autonomous centres with a multiplicity of facilities, sports, cultural, leisure facilities and public services, so that people do not feel the need to move in their daily lives. Although these issues are seen as distinct problems in research fields and policy, they are connected, requiring a holistic approach to solutions. The SymbioCity Approach supports cities in planning sustainably and identifying inclusive and innovative solutions to urban challenges through synergies between different urban systems. The approach is largely founded on practical experience and expertise from Swedish local governments. In December 2015 and with renewed support from Sida, SKL International started up the global SymbioCity Approach 2.0 programme. The main objective was to improve health, safety, comfort and quality of life for poor people living in urban areas, to address urban challenges related to sustainability and resilience. Within this context, the Global Platform for Sustainable Cities (GPSC) and the Global Program on Nature-Based Solutions for Climate Resilience aimed to bring together leading policymakers, practitioners, and experts to share knowledge, and help urban areas integrate climate and biodiversity concerns into urban development projects and investments. Cities all over the world are increasingly pursuing green sustainability agenda, to grow their economies while working to reduce carbon footprints and avoid biodiversity loss. Moreover, cities are uniquely positioned to deliver green recovery after crises and provide the foundation of resilience. In fact, the COVID-19 pandemic has highlighted the need for open green spaces in cities and access to urban nature, providing insights into future planning and policies. This approach emphasizes a multidisciplinary view, in order to make an analysis with various perspectives so that synergies between the different aspects and areas can be identified in an integrated planning framework and helps to understand how to be able to manage urban development in a way that is inclusive, holistic and a matter for all citizens; understand integrated and holistic planning so as to be able to identify synergies between urban systems; understand how to manage change through multi-level collaboration and be able to use the SymbioCity approach to improve the process and the results of urban change projects.